Water infiltration in a Dusky-Red Latosol - Falco Pruski, Fernando; Vendrame, Valmir; Feliciano de Oliveira, Edson; Balbino, Luiz Carlos; Afonso Ferreira, Paulo; Werlang, Lovânia; Torres de Carvalho, Luciano (Pesquisa Agropecuaria Brasileira, 1997)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} @font-face {font-family:"\@Arial Unicode MS"; panose-1:2 11 6 4 2 2 2 2 2 4; mso-font-charset:128; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1 -369098753 63 0 4129279 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} a:link, span.MsoHyperlink {color:blue; text-decoration:underline; text-underline:single;} a:visited, span.MsoHyperlinkFollowed {color:purple; text-decoration:underline; text-underline:single;} p {margin-right:0cm; mso-margin-top-alt:auto; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Arial Unicode MS";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The experiment was carried out with a Dusky-Red Latosol dystrophic. The method of the ring infiltrometer and four combinations of intensity and duration of rainfall with the sprinkler infiltrometer method were applied. On four consecutive days water was applied in each plot. The soil was previously prepared, and kept without vegetation during the duration of the experiment. The results showed that the velocity of infiltration and the variation of the values of velocity of infiltration obtained with the ring infiltrometer was higher than the values obtained with the remaining treatments. The velocity of infiltration diminished with successive water applications to the soil and with the increase of total precipitation applied, independently of the intensity of the precipitation.